Prevalence of anemia in under five-year-old children: a hospital-based study - Singh, Swatantar; Parihar, Sangeeta (International Journal of Contemporary Pediatrics, 2019)
Background: Anemia affects individuals of both gender and all ages, there is a need for localized and age- and context-specific studies to improve our knowledge of prevalence patterns and associated risk factors of Indian population. The present study was done to determine the prevalence of and associated risk factors for anemia in under five-year-old children in a tertiary care teaching hospital. Methods: A prospective observational study was carried out among under five-year-old children suffering from anemia. For the diagnosis of anemia, WHO criteria for haemoglobin (Hb) threshold in different age group were used. The growth and development statuses of children were evaluated by WHO’s Child Growth Standards 2006. Results: Total 240 anaemic children were enrolled into the study. Children of age group of between 2-5 years was more affected. A majority of the mother of anaemic children had primary level of school education. More than half of the children belong to lower socioeconomic classes (Class IV + Class V). Nutritional deficiency was the single most important causative factor in the development of anemia. Infectious diseases found to be more prevalent. Conclusions: Nutritional deficiency, particularly, iron deficiency is the leading cause of anemia in the present study. In addition to nutritional deficiency, socioeconomic factors like, gender, maternal education and SE class also play an important role in development of anemia.